Assessment of benthic environmental disturbance in the Ba Lai estuary using the nematode biomass spectra - Yen, Nguyen Thi My; Thai, Tran Thanh; Quang, Ngo Xuan; Ngoc Hoai, Pham (Vietnam Journal of Biotechnology, 2021)
The researchs on the biomass spectra - a functional characteristic of biotic communities is still limited. In this study, the nematode biomass spectra in the bottom of Ba Lai estuary was investigated at six subtidal stations from the sea toward the upstream. The result showed that nematode biomass spectra ranged between -8 and 1 being significantly different between stations, and the lowest biomass of those spectras was in station BL4 (< 2 µg) which is upwardly closed to the Ba Lai dam. BL4 was also characterized by the lowest nematode abundance in the studied area. In addition, station BL3 downwardly closed to the dam exhibited low number of individuals. The heterogeneity in the nematode biomass spectra of BL3 and BL4 might due to the disturbance in the sedimentary environment of Ba Lai estuary related to the dam impact. This research again supports the important role of biomass spectra as bioindicator tool for biomonitoring and environmental quality assessment. Therefore, applying nematode biomass spectra is recommended for environmental assessment due to their advantages such as timesaving, not taxonomical expertise-requirement.